2004
DOI: 10.1677/joe.0.1810393
|View full text |Cite
|
Sign up to set email alerts
|

Activities of UDP-glucuronyltransferase, beta-glucuronidase and deiodinase types I and II in hyper- and hypothyroid rats

Abstract: We have investigated the hypothesis that uridine 5 -diphosphate (UDP)-glucuronyltransferases (UGTs) and -glucuronidase are jointly involved in a mechanism for the storage and mobilization of iodothyronine metabolites in liver, kidney, heart and brain. Specifically, we predicted UGT activities to decrease and increase respectively, and -glucuronidase activity to increase and decrease respectively in hypo-and hyperthyroidism. To this end we have studied the effects of thyroid status on the activities of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Extrapolating from the observations that H9c2(2-1) cells preferentially take up thyroid hormone glucuronides, and that these stimulate the myoblast differentiation, it can be hypothesized that cardiac muscle cells are targets for a paracrine action of cardiofibroblasts mediated by glucuronidated metabolites of thyroid hormones. We measured considerable ␤-glucuronidase activities in adult-rat whole-heart homogenates (van der Heide et al, 2004) and H9c2(2-1) myotubes (this study), and this indicates that cardiomyocytes can regenerate thyroid hormones by deconjugation of the glucuronidated conjugates. Moreover, adult rat cardiomyocytes and H9c2(2-1) cells contain an iodothyronine deiodinase type 1 activity (van der Heide et al, 2004;van der Putten et al, 2002;Yonemoto et al, 1999), and cardiomyocytes from rat and pig a deiodinase type 2 activity as well (van der Heide et al, 2004;Wassen et al, 2004).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Extrapolating from the observations that H9c2(2-1) cells preferentially take up thyroid hormone glucuronides, and that these stimulate the myoblast differentiation, it can be hypothesized that cardiac muscle cells are targets for a paracrine action of cardiofibroblasts mediated by glucuronidated metabolites of thyroid hormones. We measured considerable ␤-glucuronidase activities in adult-rat whole-heart homogenates (van der Heide et al, 2004) and H9c2(2-1) myotubes (this study), and this indicates that cardiomyocytes can regenerate thyroid hormones by deconjugation of the glucuronidated conjugates. Moreover, adult rat cardiomyocytes and H9c2(2-1) cells contain an iodothyronine deiodinase type 1 activity (van der Heide et al, 2004;van der Putten et al, 2002;Yonemoto et al, 1999), and cardiomyocytes from rat and pig a deiodinase type 2 activity as well (van der Heide et al, 2004;Wassen et al, 2004).…”
Section: Discussionmentioning
confidence: 73%
“…We measured considerable ␤-glucuronidase activities in adult-rat whole-heart homogenates (van der Heide et al, 2004) and H9c2(2-1) myotubes (this study), and this indicates that cardiomyocytes can regenerate thyroid hormones by deconjugation of the glucuronidated conjugates. Moreover, adult rat cardiomyocytes and H9c2(2-1) cells contain an iodothyronine deiodinase type 1 activity (van der Heide et al, 2004;van der Putten et al, 2002;Yonemoto et al, 1999), and cardiomyocytes from rat and pig a deiodinase type 2 activity as well (van der Heide et al, 2004;Wassen et al, 2004). Most probably, the stimulatory effect on myoblast differentiation upon exposure to thyroid hormone glucuronides are ultimately caused by T3.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…D2 is also a thiol dependent selenoprotein, however, it specifically acts on the outer ring of T4 and is relatively PTU insensitive [24][25][26]. Furthermore, a recent study showed that in the rat heart, D1 specific activity is increased fourfold and cardiac activity was detectable but not sensitive to thyroid status [27]. However, to our knowledge, only a few limited studies have been carried out to clarify the relative contribution of different tissues in the global deiodinative process.…”
Section: The Iodothyronine Monodeiodinasesmentioning
confidence: 99%